Cancer Antigen 125 Serum Level in Head and Neck Diffuse Large B-Cell Lymphoma - Igor Togar Hutabarat; Agung Dinasti Permana; Yussy Afriani Dewi (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Diffuse Large B-Cell Lymphoma (DLBCL) is the most common subtype of the Non-Hodgkin Lymphoma (LNH). Until now, lactate dehydrogenase (LDH) is the only tumor marker to assess DLBCL progression; however, increased LDH is a relatively non-specific biomarker. Cancer antigen 125 (CA-125) serum level have been used as a tumor marker in ovarian cancer. The aim of this study was to explore the possible role of CA-125 serum level as a tumor marker in head and neck DLBCL.Methods: This was an observational descriptive study among consecutively sampled DLBCL patients. CA-125 serum level examination was carried out (ADVIA Centaur CA-125II) and described along with the clinical characteristics of DLBCL patients.Results: DLBCL was mostly observed in males (54.05%), most often in the 55-65 year age group (51.3%), with stage 1 DLBCL was the most prevalent (71.9%). The mean CA-125 serum level was 22.9 U/ml and increased in patients with advanced DLBCL.Conclusions: Increased CA-125 serum level in DLBCL, especially at advanced stages, suggests that CA-125 serum level may be of benefit as a tumor marker in the head and neck DLBCL. Further study is in need to explore the role of CA-125.1. Kementerian Kesehatan Republik Indonesia. Data dan kondisi penyakit limfoma di Indonesia. InfoDatin Pusat Data dan Informasi Kementerian Kesehatan RI. 2015 [cited 2020 March 18] Available from: https://www.kemkes.go.id/resources/download/pusdatin/infodatin/infodatin-limfoma.pdf2. Dwianingsih EK, Indrawati, Hardianti MS, Malueka RG , Iswar RR, Sutapa S, et al. Histopathological features of lymphoma in Yogyakarta, Indonesia. Asian Pac J Cancer Prev. 2016;17(9):4213–16.3. Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI. Riset Kesehatan Dasar (RISKESDAS) 2013. Jakarta: Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI; 20134. Cheson BD, Fisher RI, Barrington SF, Cavalli F, Schwartz LH, Zucca E, et al. Recommendations for initial evaluation, staging, and response assessment of Hodgkin and non-Hodgkin lymphoma: the Lugano classification. J Clin Oncol. 2014; 32(27):3059–67.5. Ziepert M, Hasenclever D, Kuhnt E, Glass B, Schmitz N, Pfreundschuh, et al. Standard International prognostic index remains a valid predictor of outcome for patients with aggressive CD20+B-cell lymphoma in the rituximab era. J Clin Oncol. 2010;28(14):2373-2380.6. Gutiérrez A, Martínez-Serra J, Barceló B, Sampol A, Vinas L, Gonzales G, et al. Prognostic value of serum CA125 levels in diffuse large B-cell lymphoma: potential role of a new sex and age adjusted reference value. Int J Lab Hematol. 2010; 32(6 Pt 2): 582–9.7. Dilek I, Ayakta H, Demir C, Meral C, Ozturk M. CA 125 levels in patients with Non-Hodgkin lymphoma and other hematologic malignancies. Clin Lab Haematol. 2005;27(1):51–5.8. Memar B, Aledavood A, Shahidsales S, Ahadi M, Farzadnia, Raziee HR, et al. The prognostic role of tumor marker CA-125 in B-Cell non-Hodgkin’s Lymphoma. Iran J Cancer Prev. 2015;8(1):42–6.9. Garg S, Goyal B. Evaluation of CA-125 as a prognostic marker in patients with Non-Hodgkin’s lymphoma. International Journal of Medical and Health Research. 2017;3(4):13–5.10. Paoli CJ, Bach BA, Quach D, Tsai KT, Wong B, Kallich J. Performance status of real-world oncology patients before and after first course of chemotherapy. The Journal of Community and Supportive Oncology. 2014; 12(5):163–70.11. Yadav C, Ahmad A, D’Souza B, Agarwal A, Nandini M, Prabhu KA, et al. Serum lactate dehydrogenase in Non-Hodgkin’s lymphoma: a prognostic indicator. Indian J Clin Biochem. 2016;31(2):240–2.